Analisis tentang Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik terhadap Kinerja Karyawan. Studi Kasus: di Rumah Sakit Rajawali dan Stikes Rajawali Bandung (Yayasan Kemanusiaan Bandung Indonesia) - Fotuho Waruwu (Jurnal Manajemen Maranatha, 2017)
In order to improve the performance of an employee of an organization, such as managers and supervisors should give more attention to the motivation level of their subordinates. The managers should be pay attention to their employee’s wants and needs, the strength of his subordinates and set goals in order to satisfy their own needs. Representation of employees' interests in RS Rajawali and STIKES Rajawali believed to encourage employee’s motivation to work harder and better so that it can optimize any potential. The aim of this study is to determine the effect of intrinsic and extrinsic motivation either partially or simultaneously on the employee's performance in RS Rajawali and STIKES Rajawali. Object of this study were all employees works in RS Rajawali, 122 people from a variety of occupations such as doctors, nurses, to the non-medical staff in STIKES Rajawali, 28 people consist of lecturers and administrative staff. This type of research is descriptive quantitative research, research on the data collected and expressed in the form of numbers, although the form of qualitative data as well as supporting, such as the words or phrases that are arranged in the questionnaire, the results sentences of consultation or the interview between researcher and informant. The results showed that intrinsic motivation (82,20%) and extrinsic motivation (83,56%) has an influence on the performance of employees (76,42%) in RS Rajawali and STIKES Rajawali Bandung. However from both motivations, the most responses which give an affect of the employee’s motivation are reward or salary. Keywords: Extrinsic; Intrinsic; Motivation; Performance